THE PASSIVE STRETCHING MENURUNKAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 DI KOTA DENPASAR - Sayu Aryantari Putri Thanaya; Agung Wiwiek Indrayani; Ni Luh Nopi Andayani (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
This study was conducted to determine whether passive stretching can lower blood glucose levels in people with type 2 Diabetes Mellitus in Denpasar City. This study was an experimental study with Pre and Post Test Control Group Design. Samples of 24 people were divided into two groups; an intervention group that was given a program of passive stretching and a control group (negative control) that was given no intervention. Each group consisted of 12 samples. Data analysis was done to compare the mean difference in blood glucose drop before and after given the intervention in both groups. The results obtained were p = 0.000 (p <0.05) for the first day of study and p = 0.000 (p <0.05) for the second day of study. There was a significantly greater drop in blood glucose in the intervention group compared to the control group on both days of study (first day 27.08 mg/dL, second day 21.33 mg/dL). In conclusion, there was a significant difference in blood glucose drop between the intervention group and the control group. Passive stretching lowers blood glucose levels in people with type 2 Diabetes Mellitus.